5(1.75)-3=12x-1

Simple and best practice solution for 5(1.75)-3=12x-1 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 5(1.75)-3=12x-1 equation:



5(1.75)-3=12x-1
We move all terms to the left:
5(1.75)-3-(12x-1)=0
We add all the numbers together, and all the variables
-(12x-1)+5.75=0
We get rid of parentheses
-12x+1+5.75=0
We add all the numbers together, and all the variables
-12x+6.75=0
We move all terms containing x to the left, all other terms to the right
-12x=-6.75
x=-6.75/-12
x=1/1.7777777777778

See similar equations:

| 9x+21+3x=7 | | -6(2x-7)=6(-2x+7) | | 3x+-2=-2x+-7 | | -(2x-18)=-5x | | 0+y=49 | | 54=-18m | | 20/x=3 | | 11v=-77 | | 2/3x-90=144+45x | | 7x+3x+10=-2(3x+3) | | 5^2x^2-5x=125 | | 8(v-8)=3v-24 | | 20/x=0 | | 9x-17=x=x+23 | | -(x+3)^2=49 | | 243=94+x | | (5x-10)=3(x-4) | | -3r-3=42r | | 4y+y=134 | | 8=-18+⅜(16-40m) | | 7x2-1=62 | | -39=-5x+2(6x+9) | | 6x+56=-75 | | (2x-15)=(2x-6) | | 2(x-3)=5x+23 | | 7x-9=12x-3x | | -4x(x+3)=16 | | c2=194 | | c^2=194 | | 9^x+6= | | 28+1x=16+1x | | 0.4z-0.05=-0.09z |

Equations solver categories